General training, need for the university curriculum - Peñaloza Ramella, Walter (2016)
In this text we will deal with General training in university curricula. More so, the notion of General Formation is obscured by a series of unfortunate ideas and definitions that have generated confusion among university professors. It is therefore appropriate to delimit concepts and separate what is General Formation and distinguish it from other curricular structures with which it is sometimes mixed improperly.